Paracetamol Supplementation Does Not Alter The Antitumor Activity and Lung Toxicity of Bleomycin - Suddek, Ghada M.; Salem, Hatem A.; Badary, Osama A.; Gameil, Nariman M.; El-Kashef, Hassan A. (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
Bleomycin (BLM) is well known by its antitumor activity both in vitro and in vivo. However, pulmonary fibrosis has been considered the dose limiting toxicity of the drug. Hyperpyrexia following injection of BLM was reported thus, paracetamol is sometimes administered with BLM as antipyretic drug. Actually, paracetamol was found to interfere with cytotoxicity of some drugs. This study was conducted to investigate the effect of paracetamol administration on the antitumor and lung toxicity of BLM. The antitumor activity was evaluated both in vitro and in vivo using Ehrlich ascites carcinoma (EAC) cells. Paracetamol did not alter the antitumor effect of BLM in vitro or in vivo. The lung toxicity of BLM was evidenced by decrease in the body weight, increase in the lung/body weight ratio, decrease in the response of pulmonary arterial rings to 5-hydroxytryptamine (5-HT) and increase in the contractility of tracheal smooth muscles induced by acetylcholine (ACh). The toxicity was also confirmed biochemically by marked increases in hydroxyproline and lipid peroxidation in rat lung and the decrease in reduced glutathione (GSH) level. Pretreatment with paracetamol did not significantly change lipid peroxidation, GSH level, percent survival of rats or the response of pulmonary arterial rings and tracheal smooth muscles to 5-HT and ACh respectively. The results of the present study indicated that paracetamol neither modified the antitumor effect of BLM nor changed drug-induced lung toxicity.